Assessment of mother's Knowledge, practices and believes toward home management of Neonatal jaundice in two pediatric teaching hospitals: دراسة معرفة وممارسات ومعتقدات الأم حول علاج اليرقان الوليدي في البيت في مستشفيين تعليميين للأطفال - Hameed, Numan Nafie; Abdul-Hussain, Noor Jaafar; Ahmed, Muna Essam; Kadhim, Noor-Al Huda Raheem (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Neonatal jaundice (NNJ) is one of the most common diseases globally. It is  believed  that  delays  in  detection and  improper  treatment  of  neonatal  jaundice  can  be  responsible  for  neonatal  morbidity  and  mortality.  Knowledge and  health  seeking  behavior  of  mothers  play  an  important  role in  the course  of  this  health  condition.Objectives: To study mother's knowledge and her health seeking behavior toward home management of neonatal jaundice. Methods: A cross sectional study of non-probability convenience sample of 200 mothers of neonates with neonatal jaundice who were admitted to Children Welfare Teaching Hospital and Ibn Al-Baladi Maternal and Child Hospital during the period from 1st of July to 1st of October, 2018. Data were obtained by the researcher through direct interview of the mothers and completed the structural questionnaire. Data were analyzed by SPSS through measuring frequencies, percentage, T test and chi square test. Results: The study found that high percentage of mother's were primary school graduates (38.5%), were unemployed (90%), continue the breastfeeding for NNJ (94.5%).Only (34.0%) of mothers knew the cause, (71.5%) correctly identified neonatal jaundice, (80%) exposed the child to florescent-light, (69%) use yellow beads, (69.5%) avoid using yellow color for baby clothes and (69.0%) avoid using yellow color for baby tools.  There were significant association between mothers` knowledge and mothers` age (p=0.005), education (p=0.029) and residency area (p=0.010), and between mothers` practice and occupation (p=0.039) and residency area (p=0.030), and between mothers' believes and education (p=0.001) and occupation (p=0.031).Conclusions: There are gaps in mothers' knowledge and health seeking behavior regarding neonatal jaundice as there are Fair to poor level for majority of the knowledge items, Slightly good level of mother's practices and High percentage of mothers still believed in the traditional methods regarding home management of neonatal jaundice .The suboptimal and inadequate knowledge of the mothers for majority of items was significantly associated with age and educational level of mothers. There was significant correlation of mothers’ seeking behaviors with occupation and educational level.